2017
DOI: 10.1088/1748-605x/aa6a26
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline-loaded coaxial nanofiber coating of titanium implants enhances osseointegration and inhibitsStaphylococcus aureusinfection

Abstract: Few studies have been reported that focus on developing implant surface nanofiber (NF) coating to prevent infection and enhance osseointegration by local drug release. In this study, coaxial doxycycline (Doxy)-doped polycaprolactone/polyvinyl alcohol (PCL/PVA) NFs were directly deposited on a titanium (Ti) implant surface during electrospinning. The interaction of loaded Doxy with both PVA and PCL NFs was characterized by Raman spectroscopy. The bonding strength of Doxy-doped NF coating on Ti implants was conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 58 publications
(79 reference statements)
1
22
0
Order By: Relevance
“…28 Our previous studies demonstrated that doxy-doped NF coating effectively inhibited bacterial infection and enhanced osseointegration in a contaminated rat tibia implantation model up to eight weeks. 5 These results supported the great potential of NF coating in the enhancement of implant osseointegration.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…28 Our previous studies demonstrated that doxy-doped NF coating effectively inhibited bacterial infection and enhanced osseointegration in a contaminated rat tibia implantation model up to eight weeks. 5 These results supported the great potential of NF coating in the enhancement of implant osseointegration.…”
Section: Introductionsupporting
confidence: 58%
“…The lack of early osseointegration of uncemented implants is a significant source of TJR failures. 5 Insufficient early osseointegration causes implant instability, micromotion, osteolysis and loosening. 5 To improve both initial stability and long-term fixation/osseointegration, a bioactive and physiochemical properties of the implant surface is critical.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as the affinity of the antibiotics to the titanium surface is relatively low, antibiotics that retained on the implant surface may be reduced when antibiotics are being coated to titanium. Song and his collaborators directly deposited coaxial DOX‐doped polycaprolactone/polyvinyl alcohol (PCL/PVA) nanofibers (NFs) on a titanium (Ti) implant surface during electrospinning, which demonstrated that a DOX‐doped NF coating effectively inhibited bacterial infection and enhanced osseointegration in an infected ( Staphylococcus aureus ) tibia implantation rat model . Nevertheless, such DOX coating method required a special device, and other molecules than DOX were also loaded on the implant surface.…”
Section: Introductionmentioning
confidence: 99%
“…Song and his collaborators directly deposited coaxial DOX-doped polycaprolactone/polyvinyl alcohol (PCL/PVA) nanofibers (NFs) on a titanium (Ti) implant surface during electrospinning, which demonstrated that a DOX-doped NF coating effectively inhibited bacterial infection and enhanced osseointegration in an infected (Staphylococcus aureus) tibia implantation rat model. 9 Nevertheless, such DOX coating method required a special device, and other molecules than DOX were also loaded on the implant surface. We and Walter et al have also reported that DOX treatment on the implant surface enhances osseointegration of the implants.…”
mentioning
confidence: 99%